Структура юкстагломерулярного комплекса почек у белых крыс - Денисюк, Л.Е. (Вестник зоологии, 1976)
The juxtaglomerular complex (JAC) of the kidneys was studied in 20 albino rats by the methods of histological, histochemical and luminescence analyses applying morphometry. Definite regularity was determined between the morphometric indexes of JAC